2019
DOI: 10.1029/2018wr023006
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Runoff and Nitrogen Loads From a Watershed at Different Levels of Impervious Surface Coverage and Connectivity to Storm Water Control Measures

Abstract: Urban development of watersheds increases runoff and nitrogen loads by adding urban impervious surfaces and increasing the hydrologic connectivity of these surfaces to streams. Storm water control measures (SCMs) are designed to disrupt this connectivity by retaining water in biologically active depressions where nitrogen retention, transformation, and removal occur. This work applies a mechanistic, spatially distributed, hydroecological model (RHESSys) to a suburban watershed in Charlotte, NC, with 15% total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…Given the complexity of environmental systems and the number of variables involved, site-specific models may help elucidate wet detention pond function. Knowledge of fate and transport mechanisms has been translated into models that aim to predict pollutant concentrations and loads through stormwater systems to inform engineering and management (Elliot and Trowsdale, 2007;Vezzaro et al, 2011Vezzaro et al, , 2012Fletcher et al, 2013;Bell et al, 2019). However, it has been reviewed that improvement of biophysical models will require more monitoring data for calibration and field testing, and improved understanding of fate processes and management outcomes for a wider selection of environmental contaminants (Bertrand-Krajewski, 2007;Elliot and Trowsdale, 2007;Gold et al, 2019).…”
Section: Performance Evaluation and Criteriamentioning
confidence: 99%
“…Given the complexity of environmental systems and the number of variables involved, site-specific models may help elucidate wet detention pond function. Knowledge of fate and transport mechanisms has been translated into models that aim to predict pollutant concentrations and loads through stormwater systems to inform engineering and management (Elliot and Trowsdale, 2007;Vezzaro et al, 2011Vezzaro et al, , 2012Fletcher et al, 2013;Bell et al, 2019). However, it has been reviewed that improvement of biophysical models will require more monitoring data for calibration and field testing, and improved understanding of fate processes and management outcomes for a wider selection of environmental contaminants (Bertrand-Krajewski, 2007;Elliot and Trowsdale, 2007;Gold et al, 2019).…”
Section: Performance Evaluation and Criteriamentioning
confidence: 99%
“…For instance, RHESSys has considered the change of water routing by roads and drainage networks, which potentially alters the transpiration, runoff and delivery of water to vegetations [42,43]. RHESSys is capable of identifying a cause-effect relationship between stressors and responses in a watershed, consequently, guiding more targeted managements and monitoring strategies for urbanized basins [44].…”
Section: Urbanizationmentioning
confidence: 99%
“…However, a green infrastructure could alleviate these effects. Applying RHESSys for urbanized areas in Charlotte, USA, for example, Bell et al [44] found that stormwater management measures allowed the basin to hold nitrogen during warm months while causing net nitrogen output during cold months. Shields and Tague [43] found that an increase in impervious layers in Santa Barbara cities may cause a shortage of local vegetation water usage.…”
Section: Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot project on the Front Range of Colorado found the average annual HND to be 97% in a natural undeveloped catchment, with a runoff ratio of less than 3% [15]. Comparatively, runoff ratios in areas with residential land use typically range from 30% to 80% [16][17][18]. Per the pilot project statute, the postdevelopment runoff may be legally harvested for outdoor use because the volume was not part of the historically appropriated supply [14,19].…”
Section: Introductionmentioning
confidence: 99%